Identifying Lesbian, Gay, Bisexual, and Transgender Search Terminology: A Systematic Review of Health Systematic Reviews. - Joseph G L Lee; Thomas Ylioja; Mellanye Lackey (PLoS ONE)
Research on the health of lesbian, gay, bisexual, and transgender (LGBT) populations can provide important information to address existing health inequalities. Finding existing research in LGBT health can prove challenging due to the plethora of terminology used. We sought to describe existing search strategies and to identify more comprehensive LGBT search terminology. We iteratively created a search string to identify systematic reviews and meta-analyses about LGBT health and implemented it in Embase, PubMed/MEDLINE, and PsycINFO databases on May 28-29, 2015. We hand-searched the journal LGBT Health. Inclusion criteria were: systematic reviews and meta-analyses that addressed LGBT health, used systematic searching, and used independent coders for inclusion. The published search terminology in each record and search strings provided by authors on request were cross-referenced with our original search to identify additional terminology. Our search process identified 19 systematic reviews meeting inclusion criteria. The number of search terms used to identify LGBT-related records ranged from 1 to 31. From the included studies, we identified 46 new search terms related to LGBT health. We removed five search terms as inappropriate and added five search terms used in the field. The resulting search string included 82 terms. There is room to improve the quality of searching and reporting in LGBT health systematic reviews. Future work should attempt to enhance the positive predictive value of LGBT health searches. Our findings can assist LGBT health reviewers in capturing the diversity of LGBT terminology when searching.